Quorum-Sensing in CD4+ T Cell Homeostasis: A Hypothesis and a Model - Almeida, Afonso R.; Amado, Ines F.; Reynolds, Joseph; Berges, Julien; Lythe, Grant; Molina-Paris, Carmen; Freitas, Antonio A (Frontiers in Immunology, 2012)
Homeostasis of lymphocyte numbers is believed to be due to competition between cellular populations for a common niche of restricted size, defined by the combination of interactions and trophic factors required for cell survival. Here we propose a new mechanism: homeostasis of lymphocyte numbers could also be achieved by the ability of lymphocytes to perceive the density of their own populations. Such a mechanism would be reminiscent of the primordial quorum sensing systems used by bacteria, in which some bacteria sense the accumulation of bacterial metabolites secreted by other elements of the population, allowing them to “count” the number of cells present and adapt their growth accordingly. We propose that homeostasis of CD4+ T cell numbers may occur via a quorum-sensing-like mechanism, where IL-2 is produced by activated CD4+ T cells and sensed by a population of CD4+ Treg cells that expresses the high-affinity IL-2Rα-chain and can regulate the number of activated IL-2-producing CD4+ T cells and the total CD4+T cell population. In other words, CD4+ T cell populations can restrain their growth by monitoring the number of activated cells, thus preventing uncontrolled lymphocyte proliferation during immune responses. We hypothesize that malfunction of this quorum-sensing mechanism may lead to uncontrolled T cell activation and autoimmunity. Finally, we present a mathematical model that describes the role of IL-2 and quorum-sensing mechanisms in CD4+ T cell homeostasis during an immune response.